Splash! : Ethelda Bleibtrey makes waves of change - Boxer, Elisa (Sleeping Bear Press, 2022)
"As a child with polio in the early 1900s, swimming set Ethelda Bleibtrey free. The water released her from her pain and helped her build strong muscle--and a powerful spirit. From then on, from the New York beaches to the 1920 Olympics, Ethelda made a splash wherever she went"--